2.5‐Year‐Olds Express Suspense When Others Approach Reality With False Expectations. Issue 1 (29th June 2016) - Moll, Henrike; Khalulyan, Allie; Moffett, Lillie
Abstract : The study investigated if 2.5‐year‐olds are susceptible to suspense and express tension when others' false expectations are about to be disappointed. In two experiments ( N = 32 each), children showed more tension when a protagonist approached a box with a false belief about its content than when she was ignorant. In Experiment 2, children also expressed more tension when the protagonist's belief was false than when it was true. The findings reveal that toddlers affectively anticipate the "rude awakening" of an agent who is about to discover unexpected reality. They thus not only understand false beliefs per se but also grasp the affective implications of being mistaken. The results are discussed with recourse to current theories about early understanding of false beliefs.